Single-cell RNA sequencing reveals transcriptional changes in circulating immune cells from patients with severe asthma induced by biologics - Kyungtaek Park; Ji-Hyang Lee; Eunsoon Shin; Hye Yoon Jang; Woo-Jung Song; Hyouk-Soo Kwon; Yoo Sook Cho; Jong Eun Lee; Ian Adcock; Kian Fan Chung; Jeong Seok Lee; Sungho Won; et al. (Experimental and Molecular Medicine)
Abstract Patients with severe eosinophilic asthma often require systemic medication, including corticosteroids and anti-type 2 (T2) cytokine biologics, to control the disease. While anti-IL5 and anti-IL4Rα antibodies suppress the effects of IL-4, IL-5 and IL-13, the molecular pathways modified by these biologics that are associated with clinical improvement remain unclear. Therefore, we aimed to describe the effects of T2-targeting biologics on the gene expression of blood immune cells. We conducted single-cell RNA sequencing (scRNA-seq) of peripheral blood mononuclear cells (PBMCs) from eight patients with severe eosinophilic asthma treated with mepolizumab, reslizumab, or dupilumab. PBMCs were obtained before the initiation of biologics and at 1- and 6-month timepoints after the initiation of treatment to elucidate treatment-induced changes. During treatment, the proportions of T cells/natural killer (NK) cells, myeloid cells, and B cells did not change. However, the composition of classical monocytes (CMs) changed: IL1B + CMs were reduced, and S100A + CMs were increased. The subsets of T cells also changed, and significant downregulation of the NF-κB pathway was observed. The genes related to the NF-κB pathway were suppressed across T/NK, myeloid, and B cells. The transcriptional landscape did not significantly change after the first month of treatment, but marked changes occurred at six-month intervals. In conclusion, regardless of the type of biologics used, suppression of T2-mediated pathways ultimately reduces the expression of genes related to NF-κB signaling in circulating immune cells. Further studies are warranted to identify potential biomarkers related to treatment response and long-term outcomes. Clinical trial registration number: NCT05164939